2019
DOI: 10.3390/molecules24112126
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Antibacterial Activity of Coumarin-1,2,3-triazole Hybrids Obtained from Natural Furocoumarin Peucedanin

Abstract: Synthesis of 1,2,3-triazole-substituted coumarins and also 1,2,3-triazolyl or 1,2,3-triazolylalk-1-inyl-linked coumarin-2,3-furocoumarin hybrids was performed by employing the cross-coupling and copper catalyzed azide-alkyne cycloaddition reaction approaches. The synthesized compounds were evaluated for their in vitro antibacterial activity against Staphylococcus aureus, Bacillius subtilis, Actinomyces viscosus and Escherichia coli bacterial strains. Coumarin-benzoic acid hybrids 4с, 42с and 3-((4-acetylamino-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 37 publications
0
21
0
Order By: Relevance
“…Esterification of nordentatin (1) was carried out by an acylation method [6,15] (Figure 1). First, around 100 mg of sample (1) was put in each flask.…”
Section: General Procedures For the Modification Of Nordentatin (1) Wimentioning
confidence: 99%
See 1 more Smart Citation
“…Esterification of nordentatin (1) was carried out by an acylation method [6,15] (Figure 1). First, around 100 mg of sample (1) was put in each flask.…”
Section: General Procedures For the Modification Of Nordentatin (1) Wimentioning
confidence: 99%
“…They possess a wide variety of biological activities. Coumarins and their derivatives are being extensively studied for their biological activities, low toxicity, and low drug resistance properties [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Zhengkaichen et al reported a metal-free synthesis of 1,3,5-trisubstituted-1,2,4-triazoles in the presence of iodine as catalyst (Scheme 7 ). And it can be synthesized from hydrazones and aliphatic amines under oxidative conditions via a cascade C–H functionalization, double C–N bond formation, and oxidative aromatization [ 28 ].
Scheme 7 Metal-free synthesis of 1,3,5-trisubstituted-1,2,4-triazoles in the presence of iodine as catalyst
…”
Section: Main Textmentioning
confidence: 99%
“…[ 91 ] Dimers 37a,b (MIC: 16–32 µg/ml), which showed equal activity against drug‐sensitive S. aureus and MRSA strains, were more potent than ceftazidime and ceftriaxone (MIC: 32 to >256 µg/ml). [ 92,93 ] The dimers 37 (MIC: 31.2–125 µg/ml) displayed considerable activity against two Gram‐positive bacteria ( S. pneumoniae and S. aureus ) and three Gram‐negative bacteria ( E. coli , E. aerogenes , and S. typhi ), and these two dimers 37a,b (MIC: 31.2–62.5 µg/ml) were not inferior to streptomycin (MIC: 31.2–62.5 µg/ml), kanamycin (MIC: 62.5–125 µg/ml), and vancomycin (MIC: 31.2–250 µg/ml) against all tested organisms.…”
Section: Coumarin Dimersmentioning
confidence: 99%